Nilai Psikologi Tokoh Utama Dalam Novel “Aku Tak Membenci Hujan” Karya Sry Puji Hartini - Melsa Lianti Batuk; Sanhedri Boimau; John Darwis Fallo; Ona Diana Bani (JURNAL ILMIAH RESEARCH STUDENT, 2026)
The issues raised in this study are (1) what is the psychological condition of the main character, and (2) what are the psychological values found in the novel "Aku Tak Membenci Hujan" by Sry Puji Hartini. The aim of this study is to describe the psychological condition of the main character in the novel "Aku Tak Membenci Hujan" by Sry Puji Hartini, and to describe the psychological values of the main character in the novel. The benefits of this research are (1) to contribute to the development of literary studies, particularly in the field of literary psychology, (2) to serve as a reference or comparative material for future researchers who wish to examine the novel, (3) to help readers understand the emotional and mental aspects of the main character, (4) to enhance appreciation for the work of local authors, and to highlight the messages for researchers. The theory adopted in this study is psychological theory. The data analysis method used by the author as the basis of the research analysis is the qualitative descriptive method. The data analysis technique in this study is based on the psychological dimension perspective that underlies the life of the main character. From the results of the data analysis, it can be concluded that in the novel "Aku Tak Membenci Hujan" by Sry Puji Hartini, the main character Karang Samudra exhibits psychological symptoms including trauma, dissociative amnesia, fear, and dissociative fugue. The psychological values of the main character include self-confidence, steadfastness, motivation, and empathy.